2015
DOI: 10.1038/ncomms9806
|View full text |Cite
|
Sign up to set email alerts
|

Whole-exome and targeted sequencing identify ROBO1 and ROBO2 mutations as progression-related drivers in myelodysplastic syndromes

Abstract: The progressive mechanism underlying myelodysplastic syndrome remains unknown. Here we identify ROBO1 and ROBO2 as novel progression-related somatic mutations using whole-exome and targeted sequencing in 6 of 16 (37.5%) paired MDS patients with disease progression. Further deep sequencing detects 20 (10.4%) patients with ROBO mutations in a cohort of 193 MDS patients. In addition, copy number loss and loss of heterogeneity (LOH) of ROBO1 and ROBO2 are frequently observed in patients with progression or carryin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 45 publications
2
31
0
Order By: Relevance
“…ROBO1 has in a single study been suggested as a progression-related driver in myelodysplastic syndromes, which supports the idea that the gene is a co-player in progression of haematological neoplasms [12]. In the current study, we identified two AML patients with medium expression of the gene.…”
supporting
confidence: 84%
“…ROBO1 has in a single study been suggested as a progression-related driver in myelodysplastic syndromes, which supports the idea that the gene is a co-player in progression of haematological neoplasms [12]. In the current study, we identified two AML patients with medium expression of the gene.…”
supporting
confidence: 84%
“…Stored simultaneous bone marrow aspirates were not available for the cases in the present study. Review of the literature revealed that five genes listed in Table have been reported to be downregulated in the bone marrow in percentages of AML patients: CDH1 , ID4 , ITIH5 , ROBO1 , and SFRP1 . The percentage of cases with downregulation, by methylation in the majority, varied from 14% to 63% and survival was noted to be poor among these cases.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA was isolated using a TIANamp Genomic DNA Kit (TIANGEN, Beijing, China), according to the manufacturer's instructions. Next‐generation sequencing was carried out for 28 genes using a MiSeq Benchtop Sequencer (Illumina, San Diego, CA, USA), as previously reported (Xu et al , ). These genes were found to exhibit recurrent mutations via previous whole‐exome sequencing and were also related to cancer development.…”
Section: Methodsmentioning
confidence: 99%